2021
DOI: 10.1111/puar.13423
|View full text |Cite
|
Sign up to set email alerts
|

“It Was Actually Pretty Easy”: COVID‐19 Compliance Cost Reductions in the WIC Program

Abstract: In recent years, scholars have examined the barriers to accessing public assistance benefits. Research identifies learning, compliance, and psychological costs as deterring program use. Compliance costs reflect the burdens of following program rules, which may entail providing documentation, responding to discretionary demands of bureaucrats, or attending appointments to maintain benefits. Studies identify one element of compliance costs—quarterly appointments—as a barrier to continued WIC participation. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Such flexibilities that reduce virus exposure for SNAP- and WIC-eligible individuals are particularly important given the disparities in COVID-19 infection rates driven by unequal heightened infection risks occurring among non-White and low-income households [ 12 , 13 , 14 , 15 ] who are also disproportionately impacted by food insecurity [ 16 , 17 ]. The literature shows that WIC participants are interested in telehealth options to address documented participant burdens, including travel to WIC clinic locations [ 18 ], clinic wait times [ 19 ], and finding time for appointments during clinic hours [ 20 , 21 , 22 ]. As further evidence of the importance of physical presence flexibilities for WIC participants, all states that did not have WIC electronic benefits transfer systems [ 23 ] in place prior to the onset of the pandemic and experienced resultant delays in transitioning to remote benefit issuance experienced declines in WIC participation early in the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Such flexibilities that reduce virus exposure for SNAP- and WIC-eligible individuals are particularly important given the disparities in COVID-19 infection rates driven by unequal heightened infection risks occurring among non-White and low-income households [ 12 , 13 , 14 , 15 ] who are also disproportionately impacted by food insecurity [ 16 , 17 ]. The literature shows that WIC participants are interested in telehealth options to address documented participant burdens, including travel to WIC clinic locations [ 18 ], clinic wait times [ 19 ], and finding time for appointments during clinic hours [ 20 , 21 , 22 ]. As further evidence of the importance of physical presence flexibilities for WIC participants, all states that did not have WIC electronic benefits transfer systems [ 23 ] in place prior to the onset of the pandemic and experienced resultant delays in transitioning to remote benefit issuance experienced declines in WIC participation early in the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Further, evidence suggests that these costs burden the most vulnerable and marginalized (Barnes & Henly, 2018; Chudnovsky & Peeters, 2021; Nisar, 2018) who lack the cognitive and human capital to successfully navigate these costs (Christensen et al, 2020; Döring, 2021; Herd, 2015). Given the crucial role of administrative burdens in shaping access to public benefits, examining administrative burdens, and the policy changes designed to reduce these burdens, have risen in importance during the COVID-19 pandemic (Baekgaard et al, 2021; Barnes & Petry, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although most participants in our sample had positive perceptions of the remote appointments, a few participants recalled that they faced difficulties communicating with WIC staff over the phone and missed certain aspects of in-person appointments (i.e., forming relationships with doctors). Mixed perceptions of remote appointments have also been identified in prior studies [ 12 , 33 ]. Thus, research suggests that moving forward, implementation of hybrid WIC service and appointment options may be warranted [ 23 , 38 ].…”
Section: Discussionmentioning
confidence: 70%
“…Specifically, participants perceived the remote appointments to be more efficient, and safer, than in-person appointments. Research conducted prior to the pandemic indicated that certain aspects of in-person appointments (e.g., long wait times, leaving the house with children) were burdensome for participants and made appointment attendance challenging [ 12 , 17 ]. More recent research, which was conducted after pandemic-related WIC program modifications were enacted, found that many participants were satisfied with remote options and prefer them over traditional in-person appointments [ 12 , 13 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation